In Vitro Effectiveness Test of Anti Acne Gel Formula in Combination With Natural Ingredients - WADHI, MARIA NUARI PUTRI; Bire, Winioliski Rohi; Kristiyanti, Yulia; Oeleu, Krisantus Yosef (JURNAL KESEHATAN, SAINS, DAN TEKNOLOGI (JAKASAKTI), 2025)
he development of this research aims to evaluate the antibacterial potential and formulation of Kaempferia galanga L. and Alpinia galanga L., which are plants containing ethyl para-methoxy cinnamate, flavonoids, polyphenols, and essential oils with potential antibacterial activity. The purpose of this study is to produce a stable gel formulation and determine its effectiveness. The simplicia was extracted using the maceration method with 70% ethanol as the solvent. The antibacterial activity of the extract was tested using the agar diffusion method at a concentration of 10%, followed by gel formulation with varying concentrations of the gelling agent, after which its effectiveness was assessed. The activity test results showed an inhibition zone of 9.63 mm for kencur and 10.3 mm for galangal, while the combination extract produced an inhibition zone of 12.14 mm. A stable formula was obtained at a concentration of 1.5% Carbopol 940 with an inhibitory effectiveness of 11.62 mm (Kaempferia galanga L. : Alpinia galanga L. ratio = 3 : 1), which is classified as having strong antibacterial activity.